A new indolocarbazole derivative in melanoma and carcinoma lung in vivo treatment - Anna Lantsova; Irina Golubeva; Larisa Borisova; Lyudmila Nikolaeva; Lydia Ektova; Maria Dmitrieva; Olga Orlova (BMC, 2021)
Abstract Objective The current scientific research direction is development of drugs with a targeted effect on malignant tumors. One of the promising groups is indolocarbazoles and their derivatives, which can initiate various tumor cell death pathways. Russian scientists from N. N. Blokhin National Medical Research Center of Oncology of the Ministry of Health of Russian Federation has developed a new experimental drug form of the original compound LCS 1269 with cytotoxic and antiangiogenic properties, blocking vasculogenic mimicry in tumor. The study aim is the experimental drug form LCS 1269 antitumor activity on models of transplantable mouse tumors B-16 melanoma and Lewis epidermoid lung carcinoma (LLC) with different routes and modes of administration. Material and methods Female F1 hybrid mice (C57Bl/6 x DBA/2) and male and female linear mice C57BL/6 were used for management of tumor strains. Mice were obtained from N. N. Blokhin National Medical Research Center of Oncology of the Ministry of Health of Russian Federation vivarium. The antitumor effect was assessed by tumor growth inhibition (TGI) and increase of treated animal's life span (ILS) compared to the control. Results The experimental drug form showed high antitumor activity when administered intravenously once at doses of 100 and 120 mg/kg (TGI = 98-82% and TGI = 95-77%, respectively, ILS = 24%, p < 0.05) on melanoma B-16 mice. On LLC mice, the experimental drug form showed that the intravenous administration route was effective in the range of doses from 60 to 80 mg/kg with a 5 day administration regimen with an interval of 24 h. A dose of 70 mg/kg had maximum effect at the level of TGI = 96-77% (p < 0.05) with its retention for 20 days after the end of treatment. Conclusion The studies have shown that the new compound LCS 1269 in the original drug form, has a pronounced antitumor activity and significantly reduces the volume of tumor mass both on melanoma B-16 and on LLC. It allows us to recommend continue the search for sensitivity of animal transplantable tumors to LCS 1269.